Effect Of Temperature On Flexible Printed Circuit Board During Reflow Soldering Process - Muhammad Rafiq, Mohammad Sabri (Universiti Sains Malaysia, 2018)
High demands on flexibility, lighter weight, thinner size and low cost electronic product had increases the application of Flexible Printed Circuit Board (FPCB) over Rigid Printed Circuit Board (RPCB). However, thermal factor affects significantly on FPCB during reflow soldering process. Temperature of reflow soldering process cause FPCB to encounter significant deflection and thermal stress compared to the RPCB. Therefore, the present experiment aims to investigate the effect of temperature on FPCB during reflow soldering process. The deformation of RPCB and FPCB were measured by using KEYENCE LK-G152 laser sensor placed at the entrance and outlet of reflow oven. Two temperature profile were used as variable for the experiment which is soaking temperature profile and ramp temperature profile. The result shows FPCB had low deformation with ramp temperature profile while RPCB had low deformation with soaking temperature profile. However, the deformation of FPCB is higher compared to RPCB for both temperature profile. Different in material composition of FPCB and RPCB cause the RPCB and FPCB have different preferable temperature profile. The experiment also shows that component placements pattern influences the deformation of FPCB and RPCB. For both FPCB and RPCB, component placements reduce deformation due to low wetting angle and component weight. For solder joint, FPCB solder joint has good wetting angle (<90°) which is indicate good solder paste deposited on the FPCB. However, several solder joints on FPCB are irregular in shape due to high deformation. Therefore, it is important to study the effect of temperature on FPCB during reflow soldering process for industries guideline for mass production of FPCB products.